OPTIMASI JUMLAH PRODUKSI ROTI MENGGUNAKAN PROGRAM LINEAR DAN SOFTWARE POM-QM - Rumetna, Matheus Supriyanto (Computer Based Information System Journal, 2021)
Dani Bakery factory is a factory that is engaged in non-service business, which is located at Aimas Unit 1, Sorong Regency, West Papua Province. In the midst of increasingly fierce and difficult business competition, especially when hit by the current pandemic conditions, it causes problems in determining the amount of production for a month in order to maximize profits. This study aims to solve these problems using a Linear Program, and to be more effective and efficient, Information Technology in the form of POM-QM software is used. The methods used for data collection were observation and interviews, while for data analysis using the simplex method and POM-QM software. The result is that the Dani Bakery factory gets a profit of 200,000,000 IDR per bread production every month, from which this result can be used as a reference in making decisions.